Ovarian lipid metabolic alterations in polycystic ovary syndrome: insights from proton magnetic resonance spectroscopy - Wang, Ke-Ying; Yang, Ting; Ding, Yi-Fan; Zeng, An-Rong; Li, Ying; Qiang, Jin-Wei (Frontiers in Medicine, 2025)
ObjectivesAltered ovarian lipid metabolism plays a critical role in the pathophysiology of polycystic ovary syndrome (PCOS). This study aimed to evaluate and compare ovarian lipid metabolic profiles in PCOS patients and healthy controls using proton magnetic resonance spectroscopy (1H-MRS).MethodThis was a single-center prospective study. Single-voxel 1H-MRS was used to identify the lipid metabolism in 50 PCOS patients and 40 healthy controls (training cohort). A total of 34 PCOS patients and 39 controls underwent 1H-MRS on the contralateral ovaries (test cohort). Key lipid metabolites were identified and quantified using LCModel software. A combination of these key lipids using the binary logistic regression analysis was constructed to enhance the discrimination efficiency between PCOS patients and the controls.ResultsSignificant elevations were observed in lipid metabolites MM09 + Lip09, MM14 + Lip13a + Lip13b + MM12, MM21 + Lip21, Lip23, and Lip28 (e.g., MM09, macromolecule signal at 0.9 ppm; Lip09, lipid signal at 0.9 ppm) in PCOS patients compared to controls. The combination model of key lipids achieved an AUC of 0.89 [95% confidence interval (CI): 0.83–0.95], with sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 0.76, 0.95, 0.95, and 0.76, respectively, in the training cohort, and 0.88 (95% CI, 0.80–0.95), 0.76, 0.87, 0.84, and 0.81, respectively, in the test cohort. Pathway enrichment analysis revealed significant involvement of fatty acid metabolism, phospholipid synthesis, lipid signaling, and membrane organization pathways.ConclusionThe study highlights significant lipid metabolic disruptions in PCOS. Lip23 and Lip28 emerged as potential biomarkers for PCOS diagnosis. These findings enhance the understanding of PCOS pathophysiology and provide a foundation for future targeted therapeutic approaches.